Targeting the PI3K pathway in myeloproliferative neoplasms. Issue 8 (3rd August 2022) - Gerds, Aaron T; Bartalucci, Niccolo; Assad, Albert; Yacoub, Abdulraheem
ABSTRACT: Introduction: Decreasing efficacy over time and initial suboptimal response to Janus kinase (JAK) inhibitors such as ruxolitinib in a subset of patients are critical clinical challenges associated with myeloproliferative neoplasms (MPNs), primarily myelofibrosis. Areas covered: The role of phosphatidylinositol-3 kinase (PI3K) in MPN disease progression and treatment resistance and as a potential therapeutic target in patients who experience loss of response to JAK inhibition is discussed. Understanding the complex signaling networks involved in the pathogenesis of MPNs has identified potentially novel therapeutic targets and treatment strategies, such as inhibiting other signaling pathways in addition to the JAK/signal transducer and activator of transcription (STAT) pathway. PI3K plays a crucial role downstream of JAK signaling in rescuing tumor cell proliferation, with PI3Kδ being particularly important in hematologic malignancies. Concurrent targeting of both PI3K and JAK/STAT pathways may offer an innovative therapeutic strategy to maximize efficacy. Expert opinion: Based on our understanding of the underlying mechanisms and the role of PI3K pathway signaling in the loss of response or resistance to JAK inhibitor treatment and initial results from clinical studies, the combination of parsaclisib (PI3Kδ inhibitor) and ruxolitinib holds great clinical potential. If confirmed in larger clinical trials, parsaclisib may provide more treatment options and improve clinical outcomes for patients with MPNs.